Pollen-pistil interaction in Brassica oleracea : Events prior to pollen germination. - Stead, A; Roberts, I; Dickinson, H (Springer-Verlag, 1979)
Quantitative studies of the adhesion of pollen grains to the stigma in Brassica oleracea revealed that self-pollen is initially less firmly bound than cross-pollen. The pollen grain tryphine, believed to be important in the adhesion process, has been shown to differ in mobility following self- and cross-pollination when observed using fluorescent probes. The hydration of the pollen grains has been investigated in vitro by measuring the changes in shape, volume and fresh weight of the imbibing grains. Whilst little change in volume could be detected there was a considerable increase in fresh weight together with a change of shape. The significance of these events, which occur prior to pollen germination, is discussed in relation to their effect upon subsequent germination and expression of self-incompatibility.